Effects of Sasobit/Deurex on amorphous poly alpha olefin (APAO) modified asphalt binder. (15th November 2017) - Zhao, Xiaowen; Yan, Kezhen; He, Weili; Cai, Cong
Highlights: APAO modified asphalt binders were mixed with Sasobit/Deurex. Physical, rheological properties, and microstructures were investigated. Chemical reactions might happen to the mixing of AMB with warm mix additives. Abstract: The purpose of this study aims at investigating the effect of warm-mix additive Sasobit/Deurex on properties of APAO modified asphalt binder (AMB). The physical properties were measured through penetration, softening point and ductility tests. Besides, rotational viscosity (RV), dynamic shear rheometer (DSR) and bending beam rheometer (BBR) test were utilized to determine the rheological characteristics of warm-mix asphalt binders before and after aging. Fourier transform infrared spectroscopy (FTIR) test was used to describe the chemical characteristics of Sasobit/Deurex warm-mixed APAO modified asphalt binder (AMB). The results showed that incorporation of Sasobit/Deurex into AMB could effectively reduce the viscosity and exert a distinct modification on high temperature performance of asphalt binders in terms of reduced penetration, increased softening point and decreased ductility. Dynamic shear rheometer (DSR) test showed that warm-mix asphalt had bigger complex modulus and smaller phase angle than blank AMB. Bending beam rheometer (BBR) test indicated that minor addition of Deurex (2%) have improved the low temperature rheological performance of AMB while Sasobit had negative effect on it. Moreover, the FTIR analysis showed that chemical reactions might happen during the mixing of Sasobit/Deurex with AMB. In overall consideration, 4% Sasobit and 2% Deurex were optimal dosages for the AMB in this experiment concerning the rheological characteristics, construction workability and economic benefits.